(untitled) - Chase, Stuart (London, 1955)
Administrator, educators, engineers, physicists, students of labor relations, psychologists, medical men, all sorts of people, pay increasing attention to it. The subject is urgent because of growing problems in television, telephony, radar, atomic energy, cold-war propaganda, and dealing with allies in the free world.
Keywords: Language and languages,Ngôn ngữ và ngôn ngữ